Desain Kurikulum Pendidikan Islam Integratif Berbasis Masalah untuk Penguatan Karakter dan Fokus Belajar Siswa - Fahim, Ali Masdar; Munawaroh, Saidah; Laisaan, Rasti Astuti; Acetylena, Sita (Borneo Journal of Islamic Education, 2025)
This study examines the decline in student engagement and attention in Islamic Religious Education (IRE) classes, a trend associated with excessive gadget use and the continued dominance of rote-based instruction. Using a sequential mixed-methods design, this research develops and examines a Problem-Centered Design with Emotional Intelligence (PCD+EI) framework. The initial conceptual phase constructs the PCD+EI model through an integrative review of relevant literature. The quantitative phase tests the model using a quantitative one-group pretest–posttest design, the study implements a Problem-Centered Design with Emotional Intelligence (PCD+EI) learning model in IRE lessons. The sample comprises 90 students, selected using the Isaac and Michael sampling formula with a 5% margin of error to ensure representativeness. Data were analysed using paired-samples t-tests. The results show a highly significant improvement in student engagement and cognitive learning outcomes (p < 0.001), with relatively consistent gain scores across all participating schools. These findings indicate that shifting from subject-centered instruction to a problem-centered, emotionally supportive approach can enhance students’ critical thinking and participation in learning. The study underscores the potential of integrating real-life problems, interactive instructional strategies, and emotional-intelligence components into IRE curricula. Further research involving larger and more diverse samples is recommended to validate the broader applicability of the PCD+EI model.